DIDACTIC PROVISION OF CREATIVITY DEVELOPMENT IN STUDENTS - Xotamqulova O. M. (Western European Studies, 2024)
The article talks about didactic support for the development of creativity in students
Keywords: Psychology; education; methodology; creativity